1987
DOI: 10.1007/bf00292542
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prehepatic insulin administration on alanine flux rates in diabetic dogs

Abstract: The in vivo flux rates of glucose (6-3H-glucose) and of alanine (U-14C-alanine) were measured in insulin-dependent chronically diabetic dogs which were infused with insulin employing a bedside-type artificial B cell and either the peripheral or the portal venous route. In comparison with non-diabetic control animals the diabetic dogs had near-normal patterns of glucose metabolism and pancreatic glucagon regardless of the route of insulin administration. They also showed reduced basal portal but moderately elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

1992
1992
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 36 publications
(34 reference statements)
2
22
2
Order By: Relevance
“…Isoglycaemic hyperinsulinaemic clamp data in normal and diabetic pigs after 4 weeks of peripheral and hepatic insulin delivery can remove between 50 and 75 % of insulin in the fasting state [55]. A lack of agreement exists among previous animal investigations, performed in rodents or dogs, concerning whether or not insulin delivery by the peripheral route results, as in our study, in raised [3,7,9,13,[17][18][19][20][21] or unchanged [2,6,11,[14][15][16] peripheral insulin levels. Studies in man comparing intraperitoneal and subcutaneous insulin delivery have similarly yielded conflicting results relating to the extent of systemic insulinisation [23][24][25][26][27][28]56].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Isoglycaemic hyperinsulinaemic clamp data in normal and diabetic pigs after 4 weeks of peripheral and hepatic insulin delivery can remove between 50 and 75 % of insulin in the fasting state [55]. A lack of agreement exists among previous animal investigations, performed in rodents or dogs, concerning whether or not insulin delivery by the peripheral route results, as in our study, in raised [3,7,9,13,[17][18][19][20][21] or unchanged [2,6,11,[14][15][16] peripheral insulin levels. Studies in man comparing intraperitoneal and subcutaneous insulin delivery have similarly yielded conflicting results relating to the extent of systemic insulinisation [23][24][25][26][27][28]56].…”
Section: Discussioncontrasting
confidence: 63%
“…advantage was found [2,6,9,11,14,21]. Indeed some acute experiments have shown that peripherally delivered insulin is more effective than the same dose delivered portally [1,5].…”
Section: : 1125-1134]mentioning
confidence: 99%
“…Alanine reflects both carbohydrate and protein metabolism and thus is variably affected during insulin clamps (37). In depancreatized dogs, insulin decreases alanine levels (38). In our study, the greater suppression of alanine with peripheral than portal or half peripheral infusion can be explained by higher peripheral insulin levels.…”
Section: Discussionmentioning
confidence: 45%
“…Although insulin inhibits key enzymes of gluconeogenesis (1) and the mobilization of gluconeogenic substrates to the liver (2)(3)(4)(5), it is well established that insulin-induced hypoglycemia (IIH) provokes the release of hormones (6)(7)(8)(9)(10)(11), which stimulate hepatic gluconeogenesis (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%